The Influence of Entrepreneurial Orientation on Entrepreneurial Intention Generation Z Entrepreneurship in Padang City with Openness to Experience as a Moderating Variable-: Pengaruh Entrepreneur Orientation Terhadap Entrepreneur Intention Generasi Z Berwirausaha Di Kota Padang Dengan Openess To Experience Sebagai Variabel Moderasi - Renaldy; Mike Yolanda (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
The aim of this research is to analyze (1) the influence of openness to experience on the entrepreneurial intention of GEN Z who are entrepreneurs in Padang City. (2) the influence of entrepreneurial orientation on the entrepreneurial intention of GEN Z who are entrepreneurs in Padang City. (3) the influence of entrepreneurial orientation on the entrepreneurial intention of GEN Z who are entrepreneurs in Padang City with openness to experience as a moderating variable. This type of research is quantitative descriptive research, the number of samples in this research is 130 respondents using purposive sampling techniques, data analysis methods using SEM analysis using the Smart PLS 4 application. The research results are (1) there is a significant influence between openness to experience on the entrepreneurial intention of GEN Z who are entrepreneurs in Padang City. (2) there is a significant influence between entrepreneurial orientation on the entrepreneurial intention of GEN Z who are entrepreneurs in Padang City. (3) there is a significant influence between entrepreneurial orientation on the entrepreneurial intention of GEN Z who are entrepreneurs in Padang City with openness to experience as a moderating variable